A SURVEY TO IDENTIFY FACILITY REQUIREMENTS IN THE ADMINISTRATIVE WORKPLACE - Vitasari, Prima; Gustopo, Dayal; Indriani, Sri; Sinnadurai, Suriya Kumar (Journal of Sustainable Technology and Applied Science (JSTAS), 2020)
A flexible work surrounding is recommended for the comfort of employees while doing their activities. Workplace design affects the individual who works inside it. Previous researches had revealed that physical elements in the workplace affected employees’ creativity. From these descriptions this research then making identification to physical elements that placed inside the workplace of administration staff. 150 respondents have participated in this survey. Questionnaires of this research have 13 questions where some of the questions asking about computer sets also type of office equipment that employees usually use in their work. The result of this research showed that most employees have sufficient work facility which is a computer set with LCD monitor where its screen size is adjusted according to the work demand (19 inches), and the computer lifespan is relatively ranging from five years. While type identification and computer function consider being appropriate for their job desk. From placement or setting of work, facilities give a description that average employees want computers placed at the center of the desk and put other work equipment on the right side of the desk. The result of this survey is expected able to give a significant contribution to workplace design that suitable for administration staff.